Takotsubo kardiomiopatija kao posledica aneurizmatskog subarahnoidalnog krvarenja - Milaković, Branko; Nastasović, Tijana; Lepić, Milan; Novaković, Nenad; Matić, Siniša; Rasulić, Lukas; Savić, Andrija (Vojnosanitetski pregled, 2021)
Abstract Introduction. Subarachnoid haemorrhage (SAH) can be followed by cardiac abnormalities. We describe a patient with Takotsubo cardiomyopathy and neurogenic pulmonary edema (NPE) after aneurysmal SAH. Case report. A previously healthy, postmenopausal woman, suffered from aneurysmal SAH with consequent hydrocephalus. After external ventricular drainage, craniotomy and clipping of the posterior inferior cerebellar artery aneurysm, the patient developed acute heart failure and NPE. Transthoracic echocardiogram showed the left ventricular apical ballooning and hypercontractile basal segments. On chest radiography, bilateral pulmonary infiltrates were seen. Seventeen days after the SAH attack, the patient was discharged from hospital. Postponed coronary angiography revealed no signs of coronary artery disease. Conclusion. This case and review of the relevant literature suggest that Takotsubo cardiomyopathy and neurogenic pulmonary edema are not uncommon after aneurysmal SAH.
Keywords: coronary angiography; diagnosis; echocardiography; pulmonary edema; subarachnoid hemorrhage; takotsubo cardiomiopathy; ventricular function, left